Predation, reoccupation, cannibalism, and scavenging? Records of small mammals in arctic ground squirrel middens from east Beringia - Scott L. Cocker; Grant D. Zazula; Elizabeth Hall; Christopher N. Jass; John E. Storer; Duane G. Froese (Arctic, Antarctic, and Alpine Research)
Faunal remains from fossil arctic ground squirrel (Urocitellus parryii) middens provide insight into the composition of small mammal communities during the late Pleistocene of Yukon Territory. We evaluated skeletal remains present in 88 of 249 middens in addition to fecal remains from fourteen sites across the Klondike goldfields. Two temporally distinct populations of U. parryii middens were identified from middens in association with Dawson tephra (~30,000 yr B.P.) and Sheep Creek Klondike tephra (~80,000 yr B.P.) containing the remains of arctic ground squirrels, voles (Microtus sp. M. longicaudus, M. miurus, M. xanthognathus), collared lemmings (Dicrostonyx sp. D. groenlandicus), true lemmings (Lemmus sp.), birds (Indet. Aves), and larger unidentified bones. These remains provide a unique look into the fossorial life histories of U. parryii and other small mammals of eastern Beringia within an established chronological framework. We interpret that the assemblages could represent reoccupation of middens by arvicolines or that arvicolines fell prey to hungry arctic ground squirrels and/or were incorporated into the middens as a result of opportunistic scavenging. The presence of bird bones and indeterminate bones larger than arctic ground squirrels indicates that the scavenging behavior observed in modern arctic ground squirrel populations occurred in ancient populations.